평생교육담당자를 위한 프로그램 평가준거 개발 - 방정은(Jungeun Bang); 서희정(Heejung Seo) (평생학습사회, 2015)
본 연구의 목적은 평생교육 현장의 담당자가 자체적으로 프로그램을 평가하여 질 관리를 제고할 수 있도록 실용적인 평생교육 프로그램 평가준거를 개발하는 데 있다. 연구의 목적을 달성하기 위해 평생교육 프로그램 및 프로그램 평가와 관련된 문헌을 탐색하고 CIPP 평가모형의 상황평가, 투입평가, 과정평가, 산출평가에 따른 평가준거의 초안을 설계하였다. 도출된 초안의 타당성을 검증하기 위해 53명의 실천현장 전문가와 프로그램 및 평가 관련 내용 전문가를 대상으로 3차에 걸쳐 델파이 조사를 실시하였고, 지속적인 수정․보완의 과정을 거쳐 내용타당도를 확보하였다. 이를 통해 상황평가의 2개 평가영역과 8개 평가준거, 투입평가의 4개 평가영역과 14개 평가준거, 과정평가의 1개 평가영역과 8개 평가준거, 산출평가의 2개 평가영역과 13개 평가준거, 최종 9개의 평가영역 및 43개의 평가준거로 구성된 평생교육 프로그램 평가준거 체계가 확정되었다. 최종 확정된 개별 평가준거가 내포하고 있는 의미를 구체적으로 서술하여 평생교육 현장에서의 활용성을 높일 수 있도록 하였다. The purpose of this study was to develop practical evaluation criteria for lifelong educational program so that lifelong education practitioner can improve the control of quality by evaluating the program by himself/herself. To achieve the goal of the study, references related with lifelong educational program and its evaluation were researched and a rough draft for evaluation criteria was provided based on the context evaluation, input evaluation, process evaluation, and product evaluation of CIPP evaluation model. To prove the reasonability of the provided rough draft, Delphi-survey of three times was applied towards fifty-three experts in the practical field and in evaluation and contents, and the reasonability was achieved through constant amendment and supplementation. The system of evaluation criteria for lifelong educational program, which is composed of nine evaluation areas and forty-three evaluation criteria in total including two evaluation areas and eight evaluation criteria regarding context evaluation, four evaluation areas and fourteen evaluation criteria regarding input evaluation, one evaluation area and eight evaluation criteria regarding process evaluation, two evaluation areas and thirteen evaluation criteria regarding product evaluation, was provided through the above process. The included meanings of finally confirmed each evaluation criteria were explained in concrete so that evaluation criteria for lifelong educational program can be used as much as possible in the field. KCI Citation Count: 6